2001
DOI: 10.1152/jappl.2001.90.4.1441
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory dynamics during laughter

Abstract: Lung and chest wall mechanics were studied during fits of laughter in 11 normal subjects. Laughing was naturally induced by showing clips of the funniest scenes from a movie by Roberto Benigni. Chest wall volume was measured by using a three-dimensional optoelectronic plethysmography and was partitioned into upper thorax, lower thorax, and abdominal compartments. Esophageal (Pes) and gastric (Pga) pressures were measured in seven subjects. All fits of laughter were characterized by a sudden occurrence of repet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 10 publications
0
38
1
1
Order By: Relevance
“…While a number of studies have reported that laughing is strongly associated with exacerbations of asthma [13,14] there is no current literature on laugh-induced coughing. Possible mechanisms responsible include sudden changes in lung and chest wall mechanics during laughter [15] or in relation to the specific type of humorous stimulation involved and its processing with the cortex (John Widdicombe, personal communication).…”
Section: Clinical Features Of Coughmentioning
confidence: 99%
“…While a number of studies have reported that laughing is strongly associated with exacerbations of asthma [13,14] there is no current literature on laugh-induced coughing. Possible mechanisms responsible include sudden changes in lung and chest wall mechanics during laughter [15] or in relation to the specific type of humorous stimulation involved and its processing with the cortex (John Widdicombe, personal communication).…”
Section: Clinical Features Of Coughmentioning
confidence: 99%
“…Facial, respiratory and laryngeal muscles are all recruited for laughter production 2 leading to changes in lung volume and dynamic compression of the airways. 15 These disturbances of the chest walls and other parts of the body may cause physiological changes requiring increased oxygen consumption leading to a higher HR. Logic suggests that an increase in HR and oxygen consumption should cause an increase in EE.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms have not been identified or studied, but there seem to be the two same possibilities that also apply to cough and speech. That the vigorous respiratory and laryngeal movements of laughter [45,46] activate cough sensors in the airways to reach central nervous threshold; or that cerebral cortical mechanisms, activated by particular patterns of …”
Section: Cough and Speechmentioning
confidence: 99%